PENGUKURAN KUALITAS DATA UNTUK MENINGKATKAN APLIKASI SQA DI PT XYZ - Ratna Yulika Go; Rahmi Julianasari; Ahmad Syaifulloh Imron; Yova Ruldeviyani (Universitas Nusa Cendana, 2023)
Service Quality Assurance (SQA) is one of a unit in PT XYZ an Indonesian e-commerce company. SQA is responsible for ensuring and maintaining services given to customers by Customer Service agents to meet the company's quality standard. However, the application was built without integration with the Customer Relationship Management (CRM) system, the main customer service application at PT XYZ. The problem is that if companies need SQA data, they must manually input data from SQA to CRM. This can cause vulnerabilities in the data input process. As a result, it impacts the company's business processes, which are inefficient and can be detrimental both materially and immaterially. This research aims to provide recommendations to improve the quality of SQA data so that companies can use the data to be integrated into the CRM system. The Total Data Quality Management (TDQM) method was used for this study with three dimensions: completeness, validity and accuracy. The results of each dimension are 99.64% for completeness, 84.75% for validity, and 100% for accuracy. Business rules on the validity dimension that have the lowest data quality are V1 28.57% and V6 65.11%. The problem factors were identified as an incomplete data dictionary, incomplete and obsolete SOP documents, and no business processes and data control on the application. Recommendations to improve the data quality of the application are PT XYZ can conduct an in-depth study of business roles so that all business processes can be clearly defined and regulations can be set forth in SOP documents. The use of specific reference data for each domain can be used to increase data legitimacy and the level of data suitability.